2005
DOI: 10.1007/11564751_15
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Hypertree Width: Decomposition Methods Without Decompositions

Abstract: The general intractability of the constraint satisfaction problem has motivated the study of restrictions on this problem that permit polynomial-time solvability. One major line of work has focused on structural restrictions, which arise from restricting the interaction among constraint scopes. In this paper, we engage in a mathematical investigation of generalized hypertree width, a structural measure that has up to recently eluded study. We obtain a number of computational results, including a simple proof o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 21 publications
2
83
0
1
Order By: Relevance
“…Previously, bounded hypertree width was the most general such property. Answering an open question raised in [Chen and Dalmau 2005;Cohen et al 2008;Gottlob et al 2005;Grohe 2007], we have identified a new class of polynomial-time solvable CSP instances: instances having bounded fractional edge cover number. This result suggests the definition of fractional hypertree width, which is always at most as large as the hypertree width (and in some cases much smaller).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, bounded hypertree width was the most general such property. Answering an open question raised in [Chen and Dalmau 2005;Cohen et al 2008;Gottlob et al 2005;Grohe 2007], we have identified a new class of polynomial-time solvable CSP instances: instances having bounded fractional edge cover number. This result suggests the definition of fractional hypertree width, which is always at most as large as the hypertree width (and in some cases much smaller).…”
Section: Discussionmentioning
confidence: 99%
“…For a class H of hypergraphs, we let Csp(H) be the class of all instances whose hypergraph is contained in H. The central question is for which classes H of hypergraphs the problem Csp(H) is tractable. Most recently, this question has been studied in [Chen and Dalmau 2005;Cohen et al 2008;Marx 2011;Marx 2010b;Gottlob et al 2005]. It is worth pointing out that the corresponding question for the graphs (instead of hypergraphs) of instances, in which two variables are incident if they appear together in a constraint, has been completely answered in [Grohe 2007;Grohe et al 2001] (under the complexity theoretic assumption FPT = W[1]): For a class G of graphs, the corresponding problem Csp(G) is in polynomial time if and only if G has bounded tree width.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalized hypertreewidth seems the natural counterpart of the tree decomposition method over unbounded-arity classes, and in fact CSP(A, −) is solvable in polynomial time if A has bounded hypertree-width modulo homomorphic equivalence [15]. However, it is known that generalized hypertree-width does not characterize all classes of structures where CSP(A, −) is solvable in polynomial time.…”
Section: Decision Problemmentioning
confidence: 99%
“…As an example, the degree of acyclicity of a constraint graph, measured using various graph width parameters, plays an important role with respect to the identification of tractable instances -it is known that an instance is solvable in polynomial time if the treewidth of its constraint graph is bounded by a constant [8,9,6,10,5,21]. Interestingly, even though the notion of bounded treewidth is defined with respect to tree decompositions, it is also possible to design algorithms for constraint satisfaction problems of bounded (generalized) hypertree width that do not perform any form of tree decomposition (see e.g., [3]). Other useful structural properties consider the nature of the constraints, such as their so-called functionality, monotonicity, and row convexity [7,24].…”
Section: Introductionmentioning
confidence: 99%